TANTANGAN DAN KELEBIHAN DEEP LEARNING BAGI GURU: STUDI KASUS DI SMKN 3 KOTA BIMA - Islamiah, Nurul; Awwalul Nisa, Nur; Zulaikha Az-Zahrah, Putri; Candra Dewi, Anita (STKIP Subang, 2026)
This study aims to examine the challenges and advantages of the deep learning approach for teachers at SMKN 3 Bima City. This study uses a descriptive qualitative approach with data collection techniques through open questionnaires. The results indicate several key challenges in implementing deep learning, including a shift in the teaching paradigm from teacher-centered to student-centered; time constraints in adapting curriculum targets; difficulties in developing teaching modules and authentic assessments; limited facilities and infrastructure, particularly internet access; low student motivation and inappropriate use of AI; and the complexity of assessing diverse products. On the other hand, the deep learning approach also offers various benefits, such as increasing student engagement and motivation, developing critical thinking and creativity, creating meaningful and contextual learning, and encouraging independent learning. Therefore, it can be concluded that although the implementation of deep learning faces various challenges, this approach has significant potential to improve the quality of learning if supported by teacher preparedness, adequate facilities, and ongoing training.